THE INFLUENCE OF INVESTIGATION GROUP TYPE COOPERATIVE LEARNING ON THE CRITICAL THINKING ABILITY OF STUDENTS OF THE ISLAMIC RELIGIOUS EDUCATION PROGRAM UNIVERSITY OF SINGAPERBANGSA KARAWANG - Makbul, M.; Ferianto, Ferianto; Husain, Nurjannah; Farida, Nur Aini; Munafiah, Nida'ul (Conciencia, 2024)
This research aims to determine the effect of group investigation learning (X) on the critical thinking abilities (Y) of PAI undergraduate students at Singaperbangsa University Karawang. The research method used a quantitative approach with a relational study type, and the research population was 1140 students with a purposive sampling technique. The research sample was set at 110 students; the instruments used were questionnaires and project-based performance test results. Group Investigation Cooperative Learning, 16% in the low category, 69% in the medium category, and 15% in the high category. So, the cooperative learning group, the Investigation of Islamic Religious Education students, is in the medium category. Students' critical thinking ability is 7% in the low category, 79% in the medium category, and 14% in the high category. So, learning essential thinking skills for Islamic Religious Education students is in the medium category. The R Square value = 0.756; thus, it can be concluded that there is an influence of group investigation learning (X) on critical thinking abilities (Y) of PAI S-1 students at Singaperbangsa University Karawang of 75.6%. In comparison, 24.4% is influenced by other variables that are not variables in this research.